Automation of the vacuum assisted resin transfer molding process for recreational composite yachts. Issue 11 (13th October 2015) - Swan, Sam; Yuksel, Tolga; Kim, Dave; Gurocak, Hakan
Abstract : The use of glass fiber reinforced plastics (GFRP) in large primary marine structures has noticeably increased due to their favorable stiffness, strength, durability, and manufacturability. However, GFRP construction can become cost‐prohibitive at the superyacht‐scale (36–60 m) as defects and labor intensiveness increase. In this paper, we presented an automated vacuum assisted resin transfer molding process (VaRTM) that can be integrated into an existing setup for manufacturing recreational composite yachts in the 49‐meter range. The objective of automating the system is to reduce defects and labor intensity. The developed automation system consisted of a controller, resin supply lines with valves, and infrared sensors. The control software, valves and sensors were custom developed. The system automatically monitors and adjusts resin flow in the mold in real‐time to mitigate flow front variations. The system was used to run three different scenarios common in marine composites manufacturing using VaRTM; a flat plate with consistent ply sequence, a flat plate with varying ply sequence, and a scaled yacht keel section. Results indicated that use of the automated setup improved overall evenness of resin flow and limited unwanted convergence compared to the traditional manual setup. Tensile testing indicated similar mechanical performance but greater variation in the manual sample. Voids were discovered in regions of flow convergence of the manual panel and reflected slightly more varied tensile properties as compared to automated panels. POLYM. COMPOS., 38:2411–2424, 2017. © 2015 Society of Plastics Engineers